PENGARUH PROFITABILITAS DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Yesica Videsia; R Ery WIbowo Agung; Nurcahyono Nurcahyono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to find empirical evidence about the effect of profitability, firm size, firm age, and audit opinion on the timeliness of submitting financial statements of manufacturing companies in the basic and chemical sub-sectors listed on the Indonesia Stock Exchange. The sample from this study used 30 manufacturing companies that were consistently listed on the Indonesia Stock Exchange for the period 2017 - 2019 which were taken using the purposive sampling method. Data collection in this study was carried out using the documentation method, which was done by downloading the company's annual financial information. Data analyzed by using logistic regression analysis. The results of the study identify that profitability, company size, company age, and audit opinion have a positive affect on the timeliness of submitting the company's financial statements.